Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Erastin-sensitive VDAC2 contributes to time-course peritoneal fibrosis via ferroptosis signaling induction - Wenfeng Wei; Yanping Qiu; Rong Luo; Yangping Feng (Molecular and Cellular Biochemistry, 2026)

Boosting electrochemical performance of aqueous zinc-ion batteries with high-coulombic-efficiency Zn anodes stabilized by PEG/CMC-Na crosslinked networks - Duanyi Jiang; Yanping Yang; Yanwen Zhu; Huiqin Zhang; Xiaoyan Qiu; Haizhou Yu (Chemical Engineering Journal, 2026)

Achieving 99% selective photocatalytic conversion of CO2 to CH4 via built-in electric field guided S-scheme charge transfer in UiO-66/CuS heterojunction - Jia Shi; Xiaoqing Shi; Linping Li; Kezhen Lai; Yanping Qiu; Ning Li; Yangqin Gao; Lei Ge (Chemical Engineering Journal, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Hydrothermal reduction and phase transformation of Fe(III) minerals induced by rice straw to improve the heterogeneous Fenton degradation of metolachlor - Jingyi Liu; Yu Zhao; Liulong Cheng; Zhuoye Lu; Haojie Liang; Runliang Zhu; Yue Wang; Fangxin Deng; Zhuobiao Ni; Yaying Li; Guangwei Yu; Jing Zhang; et al. (Journal of Hazardous Materials, 2025)

Effects of trigonelline, diosgenin, and Cistanche deserticola polysaccharide on the culture of female germline stem cells in vitro - Xiaoli Yu; Yikai Qiu; Jinhua Li; Yanping Zhang; Qian Wang; Zehua Jin; Xinrui Liu; Xiuying Pei (Natural Product Research, 2025)

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

Enhanced antioxidant potential of In vitro gastrointestinal digestion products derived from abalone myofibrillar protein-glucose conjugates based on structural changes - Gengxin Hao; Yanwen Ma; A.YiJiang Akemujiang; Yanping Bai; Peng Ye; Xujian Qiu; Shuting Lin (Food Bioscience, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Effect of rebar ratio, rebar diameter, cover thickness, and fiber shape on flexural and cracking behavior of rebar-reinforced UHPC beams - Minghong Qiu; Xudong Shao; Kay Wille; Yanping Zhu; Yan Wang; Yang Zhang; Zhenyu Tao (Engineering Structures, 2024)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

Design and numerical simulation of the elastomeric support for the topside modules of an FPSO - Yucu Huang; Yanping He; Yadong Liu; Ming Qiu; Mingzhi Li (Ocean Engineering, 2024)

Correction: Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2024)

Vascular plant communities and biocrusts act as controlling factors in mitigating soil erosion on the Great Wall in a semi-humid area of Northwestern China - Yanping Liu; Rongliang Jia; Wanfu Wang; Yuchen Wan; Yanhong Gao; Hongtao Zhan; Jing Ren; Zhang Chen; Fei Qiu; Jing Zhu (Science of The Total Environment, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Study of the wet-towing transportation of an FPSO with elastomeric-supporting topside modules - Yucu Huang; Yanping He; Ming Qiu; Yadong Liu; Mingzhi Li (Ocean Engineering, 2024)

Molecularly imprinted polymer sheathed mesoporous silica tube as SPME fiber coating for determination of tobacco-specific nitrosamines in water - Yuemei Chen; Yang Yu; Shaohan Wang; Jiajia Han; Mengge Fan; Yanping Zhao; Junlang Qiu; Xin Yang; Fang Zhu; Gangfeng Ouyang (Science of The Total Environment, 2024)

Separable and Inseparable Silk Fibroin Microneedles for the Transdermal Delivery of Colchicine: Development, Characterization, and Comparisons - Shiji Liao; Guirong Qiu; Yanping Hu; Bohong Guo; Yuqin Qiu (AAPS PharmSciTech, 2023)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

A review of metal contamination in seagrasses with an emphasis on metal kinetics and detoxification - Yanping Li; Fengyuan Chen; Ruojing Zhou; Xinqing Zheng; Ke Pan; Guanglong Qiu; Zhongjie Wu; Shiquan Chen; Daoru Wang (Journal of Hazardous Materials, 2023)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Impact of reinforcing ratio and fiber volume on flexural hardening behavior of steel reinforced UHPC beams - Yang Zhang; Yanping Zhu; Junfeng Qiu; Changgui Hou; Jinju Huang (Engineering Structures, 2023)

Oocyte Arrested at Metaphase II Stage were Derived from Human Pluripotent Stem Cells in vitro - Xiaoli Yu; Ning Wang; Xiang Wang; Hehe Ren; Yanping Zhang; Yingxin Zhang; Yikai Qiu; Hongyan Wang; Guoping Wang; Xiuying Pei; Ping Chen; Yahui Ren; et al. (Stem Cell Reviews and Reports, 2023)
Initiation of meiosis is the most difficult aspect of inducing competent oocytes differentiation from human stem cells in vitro . Human induced pluripotent stem cells (hiPSCs) and embryonic stem cells (hESCs) were cultured with follicle fluid, cytokines and small molecule to induced oocyte-like cells (OLCs) formation through a three-step induction procedure. Expression of surface markers and differentiation potential of germ cells were analyzed in vitro by flow cytometry, gene expression, immunocytochemistry, western blotting and RNA Sequencing. To induce the differentiation of hiPSCs into OLCs, cells were firstly cultured with a primordial germ cell medium for 10 days. The cells exhibited similar morphological features to primordial germ cells (PGCs), high expressing of germ cell markers and primordial follicle development associated genes. The induced PGCs were then cultured with the primordial follicle-like cell medium for 5 days to form the induced follicle-like structures (iFLs), which retained both primordial oocytes-like cells and granulosa-like cells. In the third step, the detached iFLs were harvested and transferred to the OLC-medium for additional 10 days. The cultured cells developed cumulus-oocyte-complexes (COCs) structures and OLCs with different sizes (50–150 μm diameter) and a zona pellucida. The in vitro matured OLCs had polar bodies and were arrested at metaphase II (MII) stage. Some OLCs were self-activated and spontaneously developed into multiple-cell structures similar to preimplantation embryos, indicating that OLCs were parthenogenetically activated though in vitro fertilization potential of OLCs are yet to be proved. in vitro maturation of OLCs derived from hiPSCs provides a new means to study human germ cell formation and oogenesis. Graphical Abstract

Effects of Calcium and Magnesium Ions on Acute Copper Toxicity to Glochidia and Early Juveniles of the Chinese Pond Mussel Anodonta woodiana - Hongbo Liu; Xiubao Chen; Yanping Su; Ik Joon Kang; Xuchun Qiu; Yohei Shimasaki; Yuji Oshima; Jian Yang (Bulletin of Environmental Contamination and Toxicology, 2016)

Contrasting patterns of river runoff and sea-ice melted water in the Canada Basin - Jinlu Tong; Min Chen; Yusheng Qiu; Yanping Li; Jianping Cao (Acta Oceanologica Sinica, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)